CAREX DRUKYULENSIS (CYPERACEAE), A 'NEW' SPECIES FROM THE HIMALAYAS (BHUTAN). (20th December 2016) - Jiménez-Mejías, P.; Noltie, H. J.
Abstract : On the basis of previously published molecular data, and morphological observations, Carex nigra subsp. drukyulensis from the eastern Himalayas (Bhutan) is raised to specific rank as Carex drukyulensis .